From Christians to Europeans: Pope Pius II and the concept of the modern Western identity - Bisaha, Nancy (Routledge, 2023)
Acknowledgements -- Timeline of ley events in Pius II's life -- Chapter 1: From Siena to Vienna: the foundations of Aeneas's worldview -- Chapter 2: 1453-1455: "Europe vs. Asia" -- Chapter 3: "The German Cardinal" at the Roman Curia -- Chapter 4: Papacy and Crusade (1458-1464) -- Conclusion -- Bibliography.